PENYUSUNAN LAPORAN KEUANGAN BERDASARKAN SAK EMKM PADA TOKO BERDIKARI DI KABUPATEN TAKALAR - S, Suharni; Tikollah, M. Ridwan; S, Masnawaty (Jurnal Sains Riset, 2024)
This study aims to determine the preparation of financial statements based on SAK EMKM at self-sufficient shops in Takalar Regency. This research is a case study at an independent shop with qualitative data types. The variable in this study is the Financial Statements Based on SAK EMKM. The population and sample in this study are independent shops in Takalar district. Data collection techniques are carried out using documentation. Data analysis techniques were carried out by (1) Designing account codes and names, (2) Making an initial trial balance of independent shops as of June 30, 2021, (3) Collecting transactions that occurred from July 1 to July 31, 2021 at independent shops, (4 ) Recording financial transactions of independent shops to journals, (5) Posting transaction journals to general ledgers, (6) Making a trial balance as of July 31, 2021, (7) Making a trial balance after adjustments/work balance, (8) Preparing financial reports (profit and loss and statement of financial position), (9) Make a closing journal and post it in the general ledger, (10) Make a trial balance after closing. Based on the results of the data anallysis carried out, it is known that Toko Berdikari has not had financial reports in accordance with existing accounting standards. This store only keeps daily records in recording daily financial transactions in the store. This indicates that the store has not implemented the recording of financial statements in accordance with Financial Accounting Standards.Keywords: Financial statements, SAK EMKM